A preparation method of a lithium ion battery negative electrode material based on ferrous oxalate

CN122950431APending Publication Date: 2026-10-20JIANGXI YIBANG NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611093442.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0003]然而,草酸亚铁负极材料在实际应用中面临多重瓶颈

Benefits of technology

[0020]本发明至少具有如下技术效果之一:1、本发明通过构建"Mn调控的Fe3O4层—Ni/Co富集的Fe3O4/Fe0复合导电层—氮掺杂碳包覆层"多级结构,实现电子传输性能与界面稳定性的协同优化。Fe3O4层引入Mn元素后,有利于调节局部晶体结构及电子传输行为;Fe3O4/Fe0复合导电层富集的Ni/Co组分在热处理过程中形成具有较高电子传输能力的复合导电区域,与铁基活性组分及氮掺杂碳层共同构建连续导电网络,降低界面电荷传输阻抗。同时,Ni/Co组分具有一定催化活性,有利于促进转化反应过程中锂化产物的可逆转化,降低极化现象,提高首次库仑效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention relates to the field of lithium-ion battery anode material technology, specifically a method for preparing lithium-ion battery anode materials based on ferrous oxalate. This method constructs a spatial gradient structure of Fe / Mn enriched regions and Ni / Co enriched regions through stepwise precipitation. A nitrogen-doped carbon coating layer is constructed by creating pores using a polyoxyethylene-polyoxypropylene ether triblock copolymer and nano-calcium carbonate dual-template, followed by impregnation and curing with methylated melamine resin. Combined with segmented heat treatment of low-temperature pre-carbonization and high-temperature carbonization, an anode material with a multi-level spatial gradient structure and hierarchical porous structure is obtained. This invention, through the synergistic effect of multi-level conductive network construction, hierarchical pore structure design, and nitrogen-doped interface modification, simultaneously improves the electronic conductivity, ion transport efficiency, and structural stability of the material, overcoming the problems of poor conductivity, significant volume effect, and insufficient cycle stability of ferrous oxalate anode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery anode material preparation technology, specifically a method for preparing lithium-ion battery anode material based on ferrous oxalate. Background Technology

[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles, and energy storage systems due to their advantages such as high energy density, long cycle life, and no memory effect. Currently, the theoretical specific capacity of commercially available graphite anodes is only about 372 mAh·g. -1 This makes it difficult to meet the ever-increasing demand for high energy density. Ferrous oxalate (FeC2O4), as a conversion-type anode material, has a theoretical specific capacity of approximately 1500 mAh·g. -1 Moreover, its raw materials are widely available and inexpensive, making it one of the important candidates for the next generation of high specific capacity anode materials.

[0003] However, ferrous oxalate anode materials face multiple bottlenecks in practical applications. First, the extremely low intrinsic electronic conductivity of ferrous oxalate leads to sluggish electrode reaction kinetics, severe polarization during high-current charge-discharge, and poor rate performance. Second, based on the conversion reaction mechanism, ferrous oxalate undergoes significant volume expansion and contraction during charge-discharge. This periodic mechanical stress easily causes particle pulverization and electrode structure damage, resulting in a sharp capacity decay. Third, during the initial charge-discharge process, a large number of lithium ions are irreversibly consumed due to the formation of a solid electrolyte interface film, leading to a low initial coulombic efficiency and reducing the actual energy density of the battery. Furthermore, the slow migration rate of lithium ions in the ferrous oxalate lattice limits the material's high-rate charge-discharge performance. These problems are interconnected—low conductivity exacerbates polarization, and volume effects accelerate structural failure; both contribute to the fact that cycle stability is far from reaching practical levels.

[0004] To overcome these shortcomings, those skilled in the art have conducted extensive research. In morphology engineering, nanosheets and porous rod-like structures can be prepared using solvothermal methods and surfactant-assisted methods to shorten lithium-ion diffusion paths and increase the exposure of active sites. However, single morphology optimization has extremely limited effect on improving electronic conductivity, and fine structures are prone to aggregation or collapse during long-term cycling. In carbon composite modification, ferrous oxalate is combined with carbon materials to attempt to build a conductive network between particles and utilize the mechanical flexibility of the carbon layer to buffer volume changes. However, conventional carbon coating often fails to achieve uniform and dense coverage, and the carbon layer lacks strong chemical bonds with the active material. After multiple charge-discharge cycles, the carbon layer is prone to peeling, losing its conductive connection and protective function. Furthermore, ordinary carbon layers lack the ability to actively regulate lithium-ion transport and may even hinder ion diffusion. In elemental doping, heterogeneous elements such as germanium and copper are introduced to improve the intrinsic conductivity or ion mobility of the material. However, doping uniformity is difficult to guarantee, and excessive doping can introduce impurities or lattice defects, which can impair long-term cycling stability. Moreover, this strategy has little effect on mitigating volume expansion and improving initial efficiency. In terms of composite structure design, attempts have been made to construct core-shell or multilayer composite systems, combining ferrous oxalate with other active or inactive materials to achieve functional complementarity. However, existing composite structures are mostly optimized for single performance indicators, lacking a systematic consideration of multiple requirements such as electronic conductivity, ionic conduction, structural stability, and interfacial compatibility; moreover, the spatial distribution of each component is poorly controllable during the preparation process, the interface problems within the core and shell layers are prominent, and it is difficult to form effective synergy between functional layers, resulting in limited overall performance improvement.

[0005] In summary, existing modification techniques have failed to simultaneously address the combined challenges of poor conductivity, significant volume effect, low initial efficiency, and insufficient cycle stability in ferrous oxalate anode materials. The overall performance of these materials still falls short of the requirements for commercial applications. Therefore, it is necessary to develop a method for preparing ferrous oxalate-based anode materials that can systematically overcome these multiple obstacles to meet the engineering demands of high-energy-density, long-life, and high-safety lithium-ion batteries. Summary of the Invention

[0006] To address the above problems, this invention provides a method for preparing a lithium-ion battery anode material based on ferrous oxalate, comprising the following steps: S1. Dissolve 20-30 parts by weight of ferrous sulfate (FeSO4·7H2O) in 80-120 parts by weight of deionized water, and stir at 300-600 rpm for 10-30 min until completely dissolved to obtain a ferrous sulfate solution, denoted as solution A; dissolve manganese salt in deionized water at a molar ratio of Fe:Mn = 1:(0.05-0.10), and stir at 300-500 rpm for 10-20 min until completely dissolved to obtain a manganese salt solution with a Mn ion concentration of 0.1-0.5 mol / L, denoted as solution B. 1. According to the molar ratio of Ni:Co=1:(0.8~1.2), the nickel salt and cobalt salt are mixed and dissolved in deionized water, and stirred at 300~500rpm for 10~20min until completely dissolved to obtain a mixed salt solution with a total Ni / Co concentration of 0.5~1.0mol / L, which is denoted as solution B2; 15~25 parts of oxalic acid (H2C2O4·2H2O) are dissolved in 100~150 parts of deionized water, and stirred at 40~50℃ and 200~400rpm for 15~30min until completely dissolved, which is denoted as solution C.

[0007] S2. Premix liquid A and liquid B1, and stir at 200-400 rpm for 5-10 min, denoted as liquid AB1. Add 5-8 parts of ammonium oxalate to liquid C, and stir at 200-400 rpm for 10-20 min to dissolve. Adjust the pH to 1.5-2.5 with 10%-25% dilute sulfuric acid to obtain the precipitate base solution. Under the conditions of 40-50℃ and stirring at 200-500 rpm, add liquid AB1 dropwise to the precipitate base solution at a rate of 1-3 mL / min. After the addition is complete, continue stirring for 1-2 h for aging. Then, maintaining the system temperature at 40-50℃, add 0.06-0.22 parts of polyvinylpyrrolidone and stir for 10-15 min. While stirring, add oxalic acid, and calculate and take the required volume of liquid B2 according to the Ni:Fe molar ratio of 1:(4-9). Slowly add liquid B2 at a dropping rate of 0.5-1 mL / min. After the addition is complete, continue stirring for 1-2 h. After the reaction is complete, filter, wash 3-5 times with deionized water, and vacuum dry to constant weight at 60-80℃ and a vacuum degree of -0.09--0.1 MPa to obtain the oxalate precursor.

[0008] S3. The oxalate precursor obtained in S2 is dispersed in an ethanol-water mixed solvent containing the first template agent, wherein the volume ratio of ethanol to water in the ethanol-water mixed solvent is (3~7):1, and stirred at 100~300 rpm for 2~4 h at room temperature; then the second template agent is added, and stirring is continued at 150~400 rpm for 1~2 h; the mixture is filtered and freeze-dried at -50℃~-30℃ to constant weight to obtain a dual-template precursor containing the first template agent and the second template agent.

[0009] S4. Prepare an ethanol solution of methylated melamine resin containing 0.5wt%~1wt% p-toluenesulfonic acid, with a concentration of 2~5wt% methylated melamine resin. Add the dual-template precursor obtained in S3 to the ethanol solution of methylated melamine resin at a solid-liquid ratio of 1:(3~5) g / mL, and stir at 100~300 rpm for 0.5~2 h. Filter, wash 2~3 times with anhydrous ethanol, vacuum dry at 50~70℃ and a vacuum degree of -0.09~-0.1MPa for 1.5~2.5 h, and then cure at 160℃ under vacuum for 1~2 h to obtain a nitrogen-carbon coated precursor. The mass of the cured methylated melamine resin in the obtained nitrogen-carbon coated precursor accounts for 5~15% of the total mass of the nitrogen-carbon coated precursor.

[0010] S5. The nitrogen-carbon coated precursor obtained in S4 is subjected to heat treatment under a protective atmosphere throughout the process. The heat treatment includes low-temperature pre-carbonization and high-temperature carbonization. Atmosphere replacement treatment is performed after low-temperature pre-carbonization, before high-temperature carbonization, and after high-temperature carbonization. After the heat treatment, the product is cooled to room temperature and dispersed in a 0.5-1.0 wt% dilute acetic acid solution. After standing for 5-10 min, it is quickly washed with deionized water until neutral and then vacuum dried at 60-80℃ and a vacuum degree of -0.09 to -0.1 MPa for 1-3 h. The purpose of the atmosphere replacement treatment after high-temperature carbonization is to remove residual decomposition gases (CO, CO2, etc.) generated during the high-temperature stage in a timely manner, accelerate the cooling rate to reduce the high-temperature residence time, and facilitate the stabilization of the heat treatment process.

[0011] Preferably, the nickel salt is one or both of nickel sulfate and nickel acetate.

[0012] Preferably, the cobalt salt is one or both of cobalt sulfate and cobalt acetate.

[0013] Preferably, the manganese salt is one or both of manganese sulfate and manganese acetate.

[0014] Preferably, the amount of oxalic acid added in S2 is 1.5 to 2.5 times the total amount of Ni / Co in liquid B2. When adding, the oxalic acid is pre-dissolved in a small amount of deionized water at 40 to 50°C to prepare a saturated solution and then slowly added dropwise to the system to prevent local oversaturation from triggering new homogeneous nucleation, thereby ensuring that the subsequent Ni / Co oxalate only grows in the outer shell layer.

[0015] Preferably, in S3, the first template agent is a polyoxyethylene polyoxypropylene ether triblock copolymer, and the second template agent is nano-calcium carbonate; the polyoxyethylene polyoxypropylene ether triblock copolymer is F127; the nano-calcium carbonate has a particle size of 20~50nm; and the mass ratio of the oxalate precursor, F127, and nano-calcium carbonate is 1:(0.1~0.2):(0.1~0.3).

[0016] Preferably, the nano-calcium carbonate undergoes surface modification treatment before use. The surface modification treatment is as follows: the nano-calcium carbonate is dispersed in anhydrous ethanol containing 1-3 wt% stearic acid, the mass-to-volume ratio of the nano-calcium carbonate to the anhydrous ethanol containing stearic acid is 1:(8-15) g / mL, stirred at 60-70℃ and 200-400 rpm for 1-2 hours, filtered, washed 2-3 times with anhydrous ethanol, and vacuum dried at 50-70℃ and a vacuum degree of -0.09 to -0.1 MPa to obtain surface-modified nano-calcium carbonate.

[0017] Preferably, the methylated melamine resin is hexamethoxymethylmelamine.

[0018] Preferably, the protective atmosphere in S5 is argon, with a basic flow rate of 80~120 mL / min; the low-temperature pre-carbonization treatment is: heating to 180~220℃ at 3~5℃ / min and holding for 1~2 hours; the atmosphere replacement treatment is: increasing the argon flow rate to 200~300 mL / min and purging for 20~40 minutes; the high-temperature carbonization treatment is: after restoring to the basic flow rate, heating to 580~620℃ at 1~3℃ / min and holding for 2~4 hours.

[0019] Preferably, the dilute acetic acid in S5 is subjected to argon bubbling for 10-20 minutes to remove oxygen before use; the settling temperature is room temperature, and after acid washing, it is quickly washed with deionized water until pH=6.5-7.0.

[0020] This invention has at least one of the following technical effects: 1. This invention constructs a "Mn-controlled Fe3O4 layer—Ni / Co enriched Fe3O4 / Fe 0 The multi-level structure of the composite conductive layer—nitrogen-doped carbon coating layer—achieves synergistic optimization of electron transport performance and interface stability. The introduction of Mn into the Fe3O4 layer helps to regulate the local crystal structure and electron transport behavior; Fe3O4 / Fe 0 During heat treatment, the Ni / Co component enriched in the composite conductive layer forms a composite conductive region with high electron transport capability. Together with the iron-based active component and the nitrogen-doped carbon layer, it constructs a continuous conductive network, reducing interfacial charge transport impedance. Simultaneously, the Ni / Co component exhibits certain catalytic activity, which is beneficial for promoting the reversible conversion of lithiation products during the conversion reaction, reducing polarization, and improving the initial coulombic efficiency.

[0021] 2. This invention utilizes the synergistic effect of template decomposition of polyoxyethylene polyoxypropylene ether triblock copolymer and acid washing removal of nano-calcium carbonate template to construct a multi-scale porous structure within and on the surface of the particles. Specifically, the space-occupying effect generated during the pyrolysis of F127 facilitates the formation of an internal mesoporous structure; the nano-calcium carbonate, after acid washing and dissolution, forms a larger pore structure. Together, these two processes increase the electrolyte wetting path, enhance the contact area between the active material and the electrolyte, and shorten the lithium-ion transport distance, thereby improving rate performance and cycle stability.

[0022] 3. This invention achieves precise and controllable conversion of oxalate precursors into target products through segmented heat treatment of low-temperature pre-carbonization and high-temperature carbonization, combined with intermediate atmosphere displacement treatment. The low-temperature pre-carbonization stage simultaneously removes water of crystallization, performs HMMM pre-crosslinking and curing, and constructs the carbon layer framework. The high-temperature stage achieves sufficient growth of Fe3O4 grains, in-situ reduction of Ni / Co components, and further ordering of the carbon layer. Atmosphere displacement effectively eliminates decomposition gases, reducing the influence of residual gases during heat treatment and improving the stability of the product composition. The nitrogen-doped carbon layer, through uniform and dense physical coating and good interfacial bonding with the surface of the active material, ensures that the coating layer does not peel off and the conductive network remains uninterrupted during long-term cycling, significantly extending cycle life. Attached Figure Description

[0023] Figure 1 This is a STEM-EDS line scan of the oxalate precursor with a spatial gradient structure of Fe / Mn enriched regions and Ni / Co enriched regions obtained in Example 1 of this invention.

[0024] Figure 2 The image shows the XRD pattern of the lithium-ion battery anode material prepared in Example 1 of this invention. Detailed Implementation

[0025] The present invention will now be described in detail through specific embodiments. However, these illustrative embodiments are for purposes and uses only to illustrate the invention and do not constitute any limitation on the actual scope of protection of the invention, nor are they intended to limit the scope of protection of the invention to these embodiments. All equivalent transformations or simple substitutions made based on the substantive content of this application should fall within the scope of protection of this application. For parameter ranges not mentioned, intermediate values ​​are selected. Furthermore, for mass percentages or weight percentages not explicitly stated or mentioned, they generally refer to the final concentration after addition.

[0026] The singular forms “for,” “or,” “a,” “any,” and “the” used in this application are intended to include the plural forms unless the context clearly indicates otherwise.

[0027] This invention first constructs an oxalate precursor with a spatial gradient structure containing Fe / Mn enrichment and Ni / Co enrichment regions via a stepwise precipitation method. Ferrous sulfate and manganese salt undergo a co-precipitation reaction in a pH buffer system composed of oxalic acid and ammonium oxalate. During the precipitation process, Mn... 2+ Mn can enter the ferrous oxalate crystal structure, regulating the precursor composition and subsequent thermal conversion process. After high-temperature heat treatment, Mn undergoes a solid-phase transformation along with the ferrous oxalate precursor and enters the Fe3O4 phase, which is beneficial for regulating the local crystal structure and electron transport behavior. It is speculated that the introduction of Mn can improve the electronic conductivity of the material by changing the local electronic environment of iron-based oxides and promoting carrier transport. At the same time, the strong bonding characteristics of Mn-O bonds are beneficial for improving the structural stability of Fe3O4 and reducing the adverse effects of lattice structure changes during cycling.

[0028] Liquid A (Fe 2+ ) and liquid B1 (Mn 2+ After pre-mixing, the mixture is added dropwise to the oxalic acid substrate. The oxalic acid / ammonium oxalate buffer system regulates the release rate of oxalate ions, causing the metal ions to precipitate gradually, which is beneficial for forming a uniformly sized and structurally stable oxalate precursor. During aging, the nascent particles further grow and tend to stabilize. After aging, polyvinylpyrrolidone (PVP) is added. The amide groups on its molecular chain are adsorbed onto the surface of the oxalate particles through coordination. On the one hand, this provides uniform nucleation sites for the subsequent epitaxial growth of the Ni / Co shell. On the other hand, PVP, as a polymeric dispersant, effectively inhibits particle aggregation through steric hindrance after adsorption onto the particle surface, thus maintaining the particle dispersion and providing uniform nucleation sites in the pre-carbonization stage. Subsequently, Ni-containing compounds are slowly added dropwise under a holding temperature of 40-50℃. 2+ and Co 2+ In liquid B2, since the surface of the existing Fe / Mn oxalate particles can serve as a heterogeneous nucleation interface, Ni / Co oxalate is more likely to deposit on the surface of existing particles than to form new crystal nuclei directly in the solution. This promotes the enrichment of Ni / Co components in the outer layer of the particles, forming an oxalate precursor with elemental spatial gradient distribution characteristics. The steric hindrance of PVP further reduces particle agglomeration, which is beneficial to maintaining the structural integrity of the precursor.

[0029] Oxalate precursors were co-dispersed with polyoxyethylene-polyoxypropylene ether triblock copolymer (F127) and nano-calcium carbonate. F127 forms aggregates in an ethanol / water mixture and adsorbs onto the surface of oxalate particles. The COC bonds in the F127 main chain undergo thermal decomposition at approximately 300–450 °C under an inert atmosphere. During subsequent heat treatment, F127 thermally decomposes, transforming its original spatially occupied regions into internal pore structures, which facilitates the formation of internal ion transport channels. Nano-calcium carbonate, after surface modification with stearic acid, is uniformly dispersed on the particle surface and shallow layers. After heat treatment, washing with dilute acetic acid causes a dissolution reaction: CaCO3 + 2CH3COOH → Ca(CH3COO)2 + H2O + CO2↑, thereby removing the calcium carbonate template and forming a surface porous structure. The synergistic effect of the two templates creates multi-scale channels within and on the surface of the material, which improves electrolyte wetting ability, increases the contact area between the active material and the electrolyte, and shortens the lithium-ion transport path, thus improving rate performance and cycle stability.

[0030] The dual-template precursor was impregnated in an ethanol solution of methyl etherified melamine resin (HMMM). Under acid catalysis, HMMM underwent a cross-linking and curing reaction, forming a continuous coating structure on the particle surface and in the porous region. During subsequent carbonization, the nitrogen-containing structure of HMMM was retained in the carbon skeleton, forming a nitrogen-containing carbon layer. The introduction of nitrogen can regulate the local electronic structure of the carbon material, improve the conductivity of the carbon layer, and enhance the interfacial bonding between the carbon layer and the active particles. The low-temperature pre-carbonization process is conducive to the formation of a stable carbon skeleton, and the intermediate atmosphere replacement treatment helps to reduce the impact of volatile decomposition products during heat treatment on the structure formation process. High-temperature carbonization further promotes the iron-based phase transformation and the stable formation of the composite structure.

[0031] The dihydrate oxalate precursor undergoes dehydration, decomposition, and solid-state transformation during heat treatment. First, ferrous oxalate loses its water of crystallization to form anhydrous ferrous oxalate, which then further decomposes to form iron oxide intermediates, releasing gaseous components such as CO and CO2. Under the influence of carbon-containing and reducing gaseous environments, the iron oxide species undergo further redox transformations, promoting the formation of Fe3O4 and Fe... 0 The structure is primarily composed of an iron-based composite phase. Simultaneously, the Ni / Co oxalate component decomposes and transforms at high temperatures, forming a Ni / Co-rich component in the outer layer of the particles, which enhances the electron transport capacity of the outer region.

[0032] In summary, this invention achieves synergistic optimization of the spatial distribution of active components, electron transport network, and ion diffusion structure through the construction of oxalate precursors with spatial gradient distribution of metal elements, the regulation of dual-template pore structure, nitrogen-doped carbon coating, and segmented heat treatment processes. Specifically, Mn element regulates the iron-based active phase structure, Ni / Co enrichment regions enhance electron transport capabilities, multi-scale pore structures improve electrolyte wetting and lithium-ion diffusion, and the nitrogen-doped carbon layer inhibits particle aggregation and maintains the stability of the conductive network, ultimately improving the material's rate performance, cycle stability, and overall electrochemical performance. Example Example 1

[0033] S1. Dissolve 25g of ferrous sulfate (FeSO4·7H2O) in 100mL of deionized water and stir at 450rpm for 20min until completely dissolved to obtain a ferrous sulfate solution, denoted as solution A; Weigh 1.22g of manganese sulfate (MnSO4·H2O) according to a Fe:Mn molar ratio of 1:0.08 and dissolve it in deionized water, transfer it to a 25mL volumetric flask and dilute to volume, stirring at 400rpm for 15min until completely dissolved to obtain a manganese salt solution with a Mn ion concentration of approximately 0.3mol / L, denoted as solution B1; According to Ni:Co = In a 1:1 molar ratio, weigh 5.26 g of nickel sulfate (NiSO4·6H2O) and 5.62 g of cobalt sulfate (CoSO4·7H2O), mix them, dissolve them in deionized water, transfer the solution to a 50 mL volumetric flask, and dilute to volume. Stir at 400 rpm for 15 min until completely dissolved to obtain a mixed salt solution with a total Ni / Co concentration of 0.8 mol / L, denoted as solution B2. Dissolve 20 g of oxalic acid (H2C2O4·2H2O) in 120 mL of deionized water and stir at 45 °C and 300 rpm for 20 min until completely dissolved, denoted as solution C.

[0034] S2. Premix liquid A and liquid B1, stir at 300 rpm for 8 min, and denote as liquid AB1; add 6 g of ammonium oxalate to liquid C, stir at 300 rpm for 15 min to dissolve, and adjust the pH to 2.0 with 20% sulfuric acid to obtain the precipitation base solution; under the conditions of 45℃ and 350 rpm stirring, add liquid AB1 dropwise to the precipitation base solution at a rate of 2 mL / min, and continue stirring for 1.5 h for aging after the addition is complete; after aging, keep the system temperature at 45℃, add 0.14 g of polyvinylpyrrolidone, and stir for 12 min; then add dropwise... Before adding liquid B2, 6.48 g of oxalic acid (H2C2O4·2H2O) was added to the system. The oxalic acid was pre-dissolved in deionized water at 45°C to prepare a saturated solution and then slowly added dropwise to the system. While stirring, 32.1 mL of liquid B2 was slowly added at a rate of 0.8 mL / min. After the addition was complete, stirring was continued for 1.5 h. After the reaction was completed, the mixture was filtered, washed four times with deionized water, and vacuum dried to constant weight at 70°C and a vacuum degree of -0.095 MPa to obtain an oxalate precursor with a spatial gradient structure of Fe / Mn enriched regions and Ni / Co enriched regions.

[0035] S3. Disperse 10g of oxalate precursor in 50mL of ethanol / water mixed solvent (42mL ethanol, 8mL water), add 1.5g of F127, and stir at 200rpm for 3h at room temperature. Before use, the nano-calcium carbonate undergoes surface modification: disperse 2.0g of nano-calcium carbonate in 18mL of anhydrous ethanol containing 2wt% stearic acid, stir at 65℃ and 300rpm for 1.5h, filter, wash three times with anhydrous ethanol, and vacuum dry at 60℃ and -0.095MPa to obtain surface-modified nano-calcium carbonate; then add 1.5g of surface-modified nano-calcium carbonate with a particle size of 35nm, and continue stirring at 280rpm for 1.5h. Filter, freeze-dry at -40℃ to constant weight to obtain a precursor containing both F127 and nano-calcium carbonate as a dual template.

[0036] S4. Prepare 100 mL of hexamethoxymethyl melamine (HMMM) ethanol solution containing 0.8 wt% p-toluenesulfonic acid (weigh 3.5 g of HMMM and 0.8 g of p-toluenesulfonic acid, and dilute to 100 mL with anhydrous ethanol). Add 10 g of the precursor containing F127 and nano-calcium carbonate dual template to 40 mL of this hexamethoxymethyl melamine ethanol solution and stir at 200 rpm for 1 h. Filter, wash three times with anhydrous ethanol, vacuum dry at 60 °C and -0.095 MPa for 2 h, and then cure at 160 °C under vacuum for 1.5 h to obtain the nitrogen-carbon coated precursor, wherein the mass of the HMMM cured product accounts for 10% of the total mass of the nitrogen-carbon coated precursor.

[0037] S5. The nitrogen-carbon coated precursor obtained in S4 was subjected to heat treatment under argon protection throughout the process, with a basic flow rate of 100 mL / min. Low-temperature pre-carbonization treatment: The temperature was increased to 200 °C at 4 °C / min and held for 1.5 h; the argon flow rate was increased to 250 mL / min and purged for 30 min for atmosphere replacement; after returning to the basic flow rate, the temperature was increased to 600 °C at 2 °C / min and held for 3 h for high-temperature carbonization treatment; after high-temperature carbonization, the atmosphere was replaced again by purging at 250 mL / min for 30 min; after heat treatment, the temperature was cooled to room temperature, and the product was dispersed in 100 mL of 0.8 wt% dilute acetic acid solution (the dilute acetic acid was treated with argon bubbling for oxygen removal for 15 min before use), allowed to stand at room temperature for 8 min, and quickly washed with deionized water until pH=7. The product was then vacuum dried at 70 °C and a vacuum degree of -0.095 MPa for 2 h to obtain the lithium-ion battery anode material.

[0038] Example 2 The difference from Example 1 is that the Fe:Mn molar ratio in S1 is 1:0.05, that is, 0.75g of manganese sulfate (MnSO4·H2O) is weighed, dissolved in deionized water, transferred to a 25mL volumetric flask and diluted to volume, and recorded as liquid B1. The rest of the preparation steps are the same as in Example 1.

[0039] Example 3 The difference from Example 1 is that the Fe:Mn molar ratio in S1 is 1:0.10, that is, 1.5g of manganese sulfate (MnSO4·H2O) is weighed, dissolved in deionized water, transferred to a 25mL volumetric flask and diluted to volume, and recorded as liquid B1. The rest of the preparation steps are the same as in Example 1.

[0040] Example 4 The difference from Example 1 is that the Ni:Co molar ratio in S1 is 1:0.8, that is, 5.82g of nickel sulfate (NiSO4·6H2O) and 4.98g of cobalt sulfate (CoSO4·7H2O) are weighed, mixed and dissolved in deionized water, transferred to a 50mL volumetric flask and diluted to volume, which is recorded as liquid B2. When adding, 28.9mL is measured, and 5.83g of oxalic acid is added. The rest of the preparation steps are the same as in Example 1.

[0041] Example 5 The difference from Example 1 is that: the Ni:Co molar ratio in S1 is 1:1.2. 4.86g of nickel sulfate (NiSO4·6H2O) and 6.24g of cobalt sulfate (CoSO4·7H2O) are weighed, mixed and dissolved in deionized water, transferred to a 50mL volumetric flask and diluted to volume, and recorded as liquid B2. 35.3mL is added dropwise, and 7.13g of oxalic acid is added. The remaining preparation steps are the same as in Example 1.

[0042] Example 6 The difference from Example 1 is that: the Ni:Fe molar ratio in S2 is 1:4. 10.52g of nickel sulfate (NiSO4·6H2O) and 11.24g of cobalt sulfate (CoSO4·7H2O) are weighed, mixed and dissolved in deionized water, transferred to a 100mL volumetric flask and diluted to volume, and recorded as liquid B2. 56.2mL is added dropwise, and 11.34g of oxalic acid is added. The remaining preparation steps are the same as in Example 1.

[0043] Example 7 The difference from Example 1 is that the Ni:Fe molar ratio in S2 is 1:9, that is, 2.63g of nickel sulfate (NiSO4·6H2O) and 2.81g of cobalt sulfate (CoSO4·7H2O) are weighed, mixed and dissolved in deionized water, transferred to a 25mL volumetric flask and diluted to volume, which is recorded as liquid B2. When adding, 25mL is measured, and the amount of oxalic acid added is 5.04g. The rest of the preparation steps are the same as in Example 1.

[0044] Example 8 The difference from Example 1 is that the amount of nano-calcium carbonate used in S3 is 1.0g, and the surface modification treatment of nano-calcium carbonate is adjusted accordingly: 1.0g of nano-calcium carbonate is dispersed in 12mL of anhydrous ethanol containing 2wt% stearic acid (0.24g of stearic acid is dissolved in 12mL of anhydrous ethanol), and the remaining preparation steps are the same as in Example 1.

[0045] Example 9 The difference from Example 1 is that: the amount of F127 used in S3 is 2.0g, the amount of nano calcium carbonate is 3.0g, and the surface modification treatment of nano calcium carbonate is adjusted accordingly: 3.0g of nano calcium carbonate is dispersed in 36mL of anhydrous ethanol containing 2wt% stearic acid (0.72g of stearic acid dissolved in 36mL of anhydrous ethanol), and the remaining preparation steps are the same as in Example 1.

[0046] Example 10 The difference from Example 1 is that: in S4, 100 mL of HMMM ethanol solution containing 0.8 wt% p-toluenesulfonic acid is prepared, that is, 5.0 g of HMMM and 0.8 g of p-toluenesulfonic acid are weighed and diluted to 100 mL with anhydrous ethanol; the mass of HMMM solidified product in the nitrogen-carbon coated precursor accounts for 15% of the total mass of the nitrogen-carbon coated precursor, and the remaining preparation steps are the same as in Example 1.

[0047] Example 11 The difference from Example 1 is that: in S5, the low-temperature pre-carbonization treatment is to raise the temperature to 180°C at 3°C / min and hold it for 2 hours; the high-temperature carbonization treatment is to raise the temperature to 580°C at 1°C / min and hold it for 4 hours; the remaining preparation steps are the same as in Example 1.

[0048] Example 12 The difference from Example 1 is that: in S5, the low-temperature pre-carbonization treatment is to raise the temperature to 220°C at 5°C / min and hold it for 1 hour; the high-temperature carbonization treatment is to raise the temperature to 620°C at 3°C / min and hold it for 2 hours; the remaining preparation steps are the same as in Example 1.

[0049] Comparative Example Comparative Example 1 The difference from Example 1 is that no manganese salt is added in S1, no liquid B1 is prepared, liquid A is used directly as liquid AB1, and the rest of the preparation steps are the same as in Example 1.

[0050] Comparative Example 2 In S1, liquid B2 is not prepared (i.e., nickel salt and cobalt salt are not added), and in S2, the dropwise addition of liquid B2 is not performed, nor is the addition of oxalic acid. The remaining preparation steps are the same as in Example 1.

[0051] Comparative Example 3 The difference from Example 1 is that the stepwise precipitation operation is cancelled in S2. Instead, liquid A, liquid B1 and 32.1 mL of liquid B2 are pre-mixed evenly to obtain a mixed salt solution. An equal amount of ammonium oxalate (6 g) as in Example 1 is added to liquid C. The pH is adjusted to 2.0 with 20% sulfuric acid. Under stirring conditions of 45°C and 500 rpm, the mixed salt solution is added dropwise to the precipitation base liquid at the same dropping rate (2 mL / min) as in Example 1. After the addition is completed, stirring is continued for 1.5 h for co-precipitation. The remaining preparation steps are the same as in Example 1.

[0052] Comparative Example 4 The difference from Example 1 is that F127 is not added in S3, and only nano-calcium carbonate is used as a template. 10g of the oxalate precursor obtained in S2 is dispersed in 50mL of ethanol / water mixed solvent (ethanol:water = 5:1, without F127), stirred at room temperature for 3h, and then 1.5g of nano-calcium carbonate (the surface modification treatment of nano-calcium carbonate is the same as in Example 1) is added. The rest of the preparation steps are the same as in Example 1.

[0053] Comparative Example 5 The difference from Example 1 is as follows: In S3, no nano-calcium carbonate is added. Only F127 is used as a template. 10g of the oxalate precursor obtained in S2 is dispersed in 50mL of ethanol / water mixed solvent containing F127 (42mL ethanol, 8mL water, 1.5g F127). After stirring at room temperature for 3h, no nano-calcium carbonate is added. Stirring is continued for 1.5h, then filtered and freeze-dried. In S5, after heat treatment, the mixture is directly cooled to room temperature without washing with dilute acetic acid. The remaining preparation steps are the same as in Example 1.

[0054] Comparative Example 6 The difference from Example 1 is that in S4, hexamethoxymethyl melamine (HMMM) is replaced with an equal mass of phenolic resin (oligomer with degree of polymerization n=3~5), and 100 mL of ethanol solution containing 5 wt% phenolic resin and 0.8 wt% p-toluenesulfonic acid is prepared. No nitrogen doping is introduced, and the remaining preparation steps are the same as in Example 1.

[0055] Comparative Example 7 The difference from Example 1 is that: in S5, low-temperature pre-carbonization and segmented heat treatment are not performed. Instead, the temperature is directly raised to 600℃ at 3℃ / min and held for 3h under argon protection (basic flow rate 100mL / min). No atmosphere replacement treatment is performed. The remaining preparation steps are the same as in Example 1.

[0056] Comparative Example 8 The difference from Example 1 is that: after the low-temperature pre-carbonization treatment in S5, no atmosphere replacement treatment is performed. Instead, the flow rate is directly restored to the basic level and the temperature is increased to 600°C at 2°C / min for high-temperature carbonization treatment. The remaining preparation steps are the same as in Example 1.

[0057] The lithium-ion battery anode materials prepared in Examples 1-12 and Comparative Examples 1-8 were tested for their first discharge specific capacity, first coulombic efficiency, rate performance, cycle stability, electrochemical impedance spectroscopy (EIS), particle size distribution, specific surface area, tap density, and powder resistivity. The results are shown in Tables 1 and 2.

[0058] Performance Test 1 The initial discharge specific capacity and initial coulombic efficiency were tested according to the constant current charge-discharge test principle and method described in GB / T 44027.1-2024. The test conditions were: voltage window 0.01~3.0V (vs. Li / Li). + The first discharge cycle (lithium insertion) was performed at a rate of 0.05C (1C = 1000mA / g, this rate setting is based on the fact that the actual reversible specific capacity range of ferrous oxalate-based conversion anode materials is 800~1400mAh / g, and 1000mAh / g is taken as the 1C benchmark rate to take into account the testing requirements of high-capacity materials). Then, the first discharge cycle (lithium insertion) was performed at the same rate (lithium removal) to 3.0V, followed by constant voltage charging to the cutoff current. The first discharge specific capacity (mAh / g) = first discharge capacity / active material mass; the first coulombic efficiency (%) = (first charge capacity / first discharge capacity) × 100%.

[0059] Performance Test 2 Rate performance was tested according to the test principle and method for capacity retention at different discharge rates as described in GB / T 44027.1-2024. The battery was subjected to 5 charge-discharge cycles at each of the following rates: 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C. The discharge specific capacity on the 5th cycle at each rate was recorded. Rate capacity retention (%) = (Discharge specific capacity at a certain rate / Discharge specific capacity at 0.1C rate) × 100%.

[0060] Performance Test 3 Cyclic stability was tested according to the cycle life test principle and method in GB / T 44027.1-2024. The battery was subjected to constant current charge-discharge cycle test at 1C rate (voltage window 0.01~3.0 V vs. Li / Li). + Record the discharge specific capacity for each cycle. Three batteries were measured in parallel for each sample, and the arithmetic mean was taken. Cycle capacity retention (%) = (1C discharge specific capacity at 300th cycle / discharge specific capacity at 1C cycle 1) × 100%.

[0061] Performance Test 4 Electrochemical impedance spectroscopy (EIS) was performed using an electrochemical workstation, following standard EIS testing methods. The test frequency range was 100 kHz to 10 mHz, with an AC perturbation signal amplitude of 5 mV, and measurements were taken at open-circuit potential. Equist plots were fitted with equivalent circuits using ZView or Nova software to obtain charge transfer impedance (Rct) and SEI film impedance (Rsei). EIS testing is used to evaluate the interfacial charge transport kinetics of the material. Performance Test 5 Particle size distribution was determined according to the provisions of Appendix A of GB / T 19077-2024 and GB / T 24533-2019. The test principle is as follows: the powder sample is dispersed in deionized water containing an appropriate amount of dispersant, and the light scattering characteristics of the particles are analyzed by laser diffraction. The volumetric particle size distribution is calculated by Mie scattering theory. The specific operation steps are as follows: weigh about 0.1~0.5g of sample and add it to 50mL of deionized water containing 0.2mL of 10% NP-40 dispersant. Disperse ultrasonically for 25min until a uniform suspension is formed. Add the suspension to the circulating dispersion system of the laser particle size analyzer, using deionized water as the dispersion medium. Start the test after the instrument's light shielding reaches a suitable range of 8%~20%. Each sample is measured in parallel 3 times, and the arithmetic mean is taken as the final result. The test results are represented by cumulative volume distribution curves, recording D10 (particle size corresponding to 10% of the cumulative volume), D50 (median diameter, particle size corresponding to 50% of the cumulative volume), and D90 (particle size corresponding to 90% of the cumulative volume).

[0062] Performance Test 6 Specific surface area was determined in accordance with the provisions of GB / T 19587-2017 and GB / T 24533-2019, Clause 6.6. The test principle is as follows: at liquid nitrogen temperature (77.3K), using nitrogen as the adsorbate, the amount of nitrogen adsorbed by the sample under different relative pressures was measured. Based on the Brunauer-Emmett-Teller (BET) multilayer adsorption theory, the specific surface area of ​​the sample was calculated from the adsorption isotherm. The specific operating steps are as follows: Weigh approximately 0.2~0.5g of sample that has been vacuum dried at 120℃ for 12h, place it in a sample tube, and degas it at 200℃ under vacuum for 2~4h to remove impurity gases adsorbed on the sample surface; place the sample tube in the test station of the specific surface area analyzer, and under liquid nitrogen bath (77.3K) conditions, using nitrogen as the adsorbate, measure the adsorption capacity at at least 5 pressure points within the relative pressure (P / P0) range of 0.05~0.30; calculate the monolayer adsorption capacity by linear fitting of the BET equation, and then obtain the specific surface area (m²). 2 / g); simultaneously, the total pore volume (cm³) was calculated using the BJH (Barrett-Joyner-Halenda) model based on the adsorption isotherm. 3 The average pore size ( / g) and average pore size (nm) were measured. Each sample was measured twice in parallel, with a relative deviation not exceeding 5%.

[0063] Performance Test 7 Tapped density was determined according to the provisions of Appendix M of GB / T 5162-2021 and GB / T 24533-2019. The test principle is as follows: a certain amount of powder is placed in a graduated cylinder, and mechanically vibrated at a specified amplitude and frequency using a vibration device until the powder volume no longer decreases. The tapped density is calculated by dividing the powder mass by the volume after vibration. Specific operating steps are as follows: Weigh approximately 50g of the dry sample (accurate to 0.01g) and carefully pour it into a 100mL graduated glass cylinder, avoiding powder adhesion to the inner wall of the cylinder; fix the cylinder on the tapped density meter, set the vibration frequency to 250 times per minute (adjustable within the range of 100-300 times / min), and the amplitude to 3mm; start the instrument vibration, and record the powder volume every 500 vibrations until the difference between two consecutive readings does not exceed 0.1mL (usually requiring 3000-5000 vibrations); tapped density (g / cm³). 3 = Sample mass (g) / Volume after tapping (mL). Each sample was measured in triplicate, and the arithmetic mean was taken as the final result.

[0064] Performance Test 8 Powder resistivity was determined according to the relevant test methods for powder compaction density and resistivity in GB / T 24533-2019 and the general test principle of the four-probe method. The test principle is as follows: the powder sample is placed in an insulating mold and compacted under constant pressure to form a columnar compact with a certain density. The resistance of the compact is measured using the four-probe method, and the powder resistivity is calculated based on the geometric dimensions of the compact. Because the density of powder materials varies, the test data differs under loose and vibrated density conditions; therefore, the powder resistivity test must be conducted under specified pressure conditions. The specific operating steps are as follows: weigh approximately 25g of dry sample and place it in the insulating mold of the powder resistivity tester; apply pressure at a constant rate to the set pressure of 30MPa, maintain the pressure stable, and measure the resistance value R (Ω) of the compact using the four-probe method. Simultaneously record the thickness h (cm) and diameter d (cm) of the compact after pressurization. The powder resistivity ρ (Ω·cm) is calculated using the following formula: ρ = R × π(d / 2) 2 / h. Each sample was measured 3-5 times under different pressures, and the average value under stable pressure was taken as the final result.

[0065] Table 1. Electrochemical performance test results of Examples 1-12 and Comparative Examples 1-8

[0066] Table 2. Test results of physical properties of Examples 1-12 and Comparative Examples 1-8

[0067] A comparison of Examples 1, 2, and 3 shows that when the Fe:Mn molar ratio increases from 1:0.05 to 1:0.08 and then to 1:0.10, the initial discharge specific capacity and initial coulombic efficiency both show a continuous upward trend, while the powder resistivity initially decreases significantly and then increases slightly. This indicates that the introduction of Mn can effectively improve the intrinsic conductivity of the material.

[0068] The comparison between Examples 4, 1 and 5 shows that when the Ni:Co molar ratio is adjusted from 1:0.8 to 1:1.0 and then to 1:1.2, the powder resistance first decreases and then increases, and the rate performance shows a trend of first increasing and then decreasing. This indicates that when Ni:Co=1:1.0, the Ni / Co synergistic effect has the most significant effect on improving conductivity and rate performance.

[0069] A comparison of Examples 6, 1, and 7 shows that as the enrichment of Ni / Co on the surface increases, the resistivity of the powder continues to decrease, while the specific surface area and initial specific capacity show an upward trend, and the rate performance first significantly improves and then tends to stabilize.

[0070] A comparison of Examples 8, 1, and 9 shows that when the amounts of F127 and nano-calcium carbonate are increased simultaneously, the specific surface area, pore volume, and average pore size continuously increase, while the rate performance first increases and then decreases. This indicates that an appropriate amount of dual template can effectively construct a hierarchical pore structure, and further increases in dosage have a saturated effect on improving the pore structure.

[0071] A comparison between Example 10 and Example 1 shows that when the thickness of the nitrogen-carbon coating increases, the cycle stability improves slightly but the specific capacity decreases slightly, indicating that the contribution of further thickening of the coating to the improvement of specific capacity tends to saturate.

[0072] A comparison of Examples 11, 1, and 12 shows that when the high-temperature carbonization temperature increases from 580℃ to 600℃ and then to 620℃, the initial discharge specific capacity and rate performance both show a trend of first increasing and then decreasing, while the powder resistivity continues to decrease, but the rate of decrease narrows. This indicates that 600℃ is a relatively optimal carbonization temperature, at which temperature the growth of Fe3O4 grains and the ordering of the carbon layer reach a good balance.

[0073] Comparative Examples 1-8 omitted one key element from each of the following: the introduction of Mn, the Ni / Co outer layer, the spatial gradient distribution structure of metal elements, the F127 template, the nano-calcium carbonate template, nitrogen doping, and segmented heat treatment and atmosphere replacement. Consequently, none of the physical properties and electrochemical performance indicators reached the level of Example 1. These results demonstrate that the multi-level synergistic design of the present invention—the spatial gradient structure of the Fe / Mn enrichment region and the Ni / Co enrichment region, the multi-level porous structure of the F127 / nano-calcium carbonate dual template, and the nitrogen-doped carbon coating layer—is indispensable. All these elements collectively endow the material with excellent comprehensive electrochemical performance.

[0074] Figure 1 This is a STEM-EDS line scan of the oxalate precursor with a spatial gradient structure of Fe / Mn enriched regions and Ni / Co enriched regions prepared in Example 1 of this invention. Figure 1 It can be seen that from the center of the oxalate precursor to the outer layer of the particle, the Fe and Mn element signals are generally highly distributed, while the Ni and Co elements are enhanced in the particle edge region, indicating that the oxalate precursor has a radial elemental gradient distribution in the Fe / Mn enrichment region and the Ni / Co enrichment region. Figure 2 The image shows the XRD pattern of the lithium-ion battery anode material prepared in Example 1 of this invention. Figure 2 It can be seen that Fe3O4 and Fe were mainly detected in the negative electrode material obtained after S5 heat treatment, pickling and drying in Example 1. 0 The characteristic diffraction peaks indicate that the oxalate precursor, after segmented heat treatment, forms a matrix mainly composed of Fe3O4 and containing Fe. 0The iron-based composite phase structure of the components; Ni, Co, Mn and nitrogen-containing carbon components did not show obvious independent diffraction peaks due to their low content, high dispersion or low crystallinity.

[0075] The above results demonstrate and describe the basic principles and main features of this application, as well as its advantages.

[0076] Those skilled in the art should understand that this application is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of this application. Various changes and modifications can be made to this application without departing from the spirit and scope thereof, and all such changes and modifications fall within the scope of this application as claimed. The scope of protection of this application is defined by the equivalents of the appended claims.

Claims

1. A method for preparing a lithium-ion battery anode material based on ferrous oxalate, characterized in that, Includes the following steps: S1. By weight, dissolve 20-30 parts of ferrous sulfate in 80-120 parts of deionized water, denoted as solution A; dissolve manganese salt in deionized water at a molar ratio of Fe:Mn = 1:(0.05-0.10) to obtain a manganese salt solution with a Mn ion concentration of 0.1-0.5 mol / L, denoted as solution B1; dissolve nickel and cobalt salts together in deionized water at a molar ratio of Ni:Co = 1:(0.8-1.2) to obtain a mixed salt solution with a total Ni / Co concentration of 0.5-1.0 mol / L, denoted as solution B2. Dissolve 15-25 parts of oxalic acid in 100-150 parts of deionized water, and denote this solution as solution C; S2. Premix liquid A and liquid B1, and denote it as liquid AB1. Add 5-8 parts of ammonium oxalate to liquid C, stir to dissolve, and adjust the pH to 1.5-2.5 to obtain the precipitate bottom solution. Add liquid AB1 dropwise to the precipitate bottom solution. After the addition is complete, age the solution. After aging, add 0.06-0.22 parts of polyvinylpyrrolidone and stir for 10-15 minutes. Keep stirring and add oxalic acid. Calculate the required volume of liquid B2 according to the Ni:Fe molar ratio of 1:(4-9) and add liquid B2 slowly. After the reaction is complete, filter, wash, and dry to obtain the oxalate precursor. S3. Disperse the oxalate precursor obtained in S2 in an ethanol-water mixed solvent containing the first template agent, with a volume ratio of ethanol to water of (3~7):1, and stir; then add the second template agent, continue stirring, filter, and freeze dry to obtain a dual-template precursor containing the first template agent and the second template agent. S4. Prepare an ethanol solution of methylated melamine resin containing 0.5wt%~1wt% p-toluenesulfonic acid, with a methylated melamine resin concentration of 2~5wt%. Add the precursor containing dual templates obtained in S3 to the methylated melamine resin ethanol solution at a solid-liquid ratio of 1:(3~5) g / mL. Filter, rinse, dry, and vacuum solidify to obtain the nitrogen-carbon coated precursor. S5. The nitrogen-carbon coated precursor obtained in S4 is subjected to heat treatment under a protective atmosphere. The heat treatment includes low-temperature pre-carbonization treatment and high-temperature carbonization treatment. Atmosphere replacement treatment is performed after low-temperature pre-carbonization treatment, before high-temperature carbonization treatment, and after high-temperature carbonization treatment. After the heat treatment is completed, the product is cooled to room temperature, dispersed in 0.5~1.0wt% dilute acetic acid solution, and allowed to stand for 5~10 min. After washing and drying, lithium-ion battery anode material based on ferrous oxalate is obtained.

2. The method for preparing a lithium-ion battery anode material based on ferrous oxalate according to claim 1, characterized in that, The nickel salt is one or both of nickel sulfate and nickel acetate.

3. The method for preparing a lithium-ion battery anode material based on ferrous oxalate according to claim 1, characterized in that, The cobalt salt is one or both of cobalt sulfate and cobalt acetate.

4. The method for preparing a lithium-ion battery anode material based on ferrous oxalate according to claim 1, characterized in that, The manganese salt is one or both of manganese sulfate and manganese acetate.

5. The method for preparing a lithium-ion battery anode material based on ferrous oxalate according to claim 1, characterized in that, The amount of oxalic acid to be added in S2 is 1.5 to 2.5 times the total amount of Ni / Co in liquid B2. When adding, the oxalic acid is first dissolved in deionized water at 40 to 50°C to prepare a saturated solution and then slowly added dropwise to the system.

6. The method for preparing a lithium-ion battery anode material based on ferrous oxalate according to claim 1, characterized in that, In S3, the first template agent is a polyoxyethylene polyoxypropylene ether triblock copolymer, the polyoxyethylene polyoxypropylene ether triblock copolymer is F127, and the second template agent is nano-calcium carbonate; the mass ratio of the oxalate precursor, F127 and nano-calcium carbonate is 1:(0.1~0.2):(0.1~0.3).

7. The method for preparing a lithium-ion battery anode material based on ferrous oxalate according to claim 6, characterized in that, The nano-calcium carbonate is surface modified before use. The surface modification is performed by dispersing nano-calcium carbonate in anhydrous ethanol containing 1-3 wt% stearic acid, wherein the mass-to-volume ratio of nano-calcium carbonate to anhydrous ethanol containing stearic acid is 1:(8-15) g / mL. The mixture is stirred at 60-70℃ and 200-400 rpm for 1-2 hours, filtered, washed 2-3 times with anhydrous ethanol, and vacuum dried at 50-70℃ and a vacuum degree of -0.09 to -0.1 MPa to obtain surface-modified nano-calcium carbonate.

8. The method for preparing a lithium-ion battery anode material based on ferrous oxalate according to claim 1, characterized in that, The methylated melamine resin is hexamethoxymethylmelamine.

9. The method for preparing a lithium-ion battery anode material based on ferrous oxalate according to claim 1, characterized in that, The protective atmosphere described in S5 is argon, with a basic flow rate of 80~120 mL / min; the low-temperature pre-carbonization treatment is: heating to 180~220℃ at 3~5℃ / min and holding for 1~2 hours; the atmosphere replacement treatment is: increasing the argon flow rate to 200~300 mL / min and purging for 20~40 minutes; the high-temperature carbonization treatment is: after restoring to the basic flow rate, heating to 580~620℃ at 1~3℃ / min and holding for 2~4 hours.

10. The method for preparing a lithium-ion battery anode material based on ferrous oxalate according to claim 1, characterized in that, The dilute acetic acid described in S5 is subjected to argon bubbling for 10-20 minutes for deoxygenation before use; the settling temperature is room temperature, and after acid washing, it is quickly washed with deionized water until pH=6.5-7.0.